Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP

Ring opening polymerization of lactide: kinetics and modeling - Metkar, Sangeeta; Sathe, Vivek; Rahman, Imran; Idage, Bhaskar; Idage, Susheela (Chemical Engineering Communications, 2019)
The ring opening polymerization (ROP) kinetics of L-lactide was studied in bulk at 150, 160, and 180 degrees C using stannous octoate [Sn(Oct)(2)] catalyst and 1-pyrene butanol co-catalyst. The effect of different parameters namely, time and co-catalyst to catalyst ratio was studied on the properties of polylactide. The experimental results showed high conversion of L-lactide. The kinetics of L-lactide ROP follows the co-ordination insertion mechanism. The experimental results obtained were studied to account for the reversible activation, propagation, termination, and validated by modeling using MATLAB. The model developed successfully predicts the monomer conversion and the kinetics of L-lactide ROP.
Keywords: 1-pyrene butanol; Average molecular weights; GPC; kinetics; L-Lactide; Modeling and simulation; Polymerization temperature; Proton NMR; ROP; Stannous octoate